Implementasi Kebijakan Perubahan Status Kampung Adat Yoboi Di Distrik Sentani Kabupaten Jayapura Provinsi Papua - Monim, Ivanna Mieske Christianny; Ilham, Muh; Suwanda, Dadang (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
Yoboi Village change of status from Government Village to Traditional Village in Jayapura Regency is expected to provide the village with greater opportunities in managing its own area. The purpose of this study is to determine and to analyze the supporting and inhibiting factors for implementing policies to change the status of Yoboi traditional village in Sentani District, Jayapura Regency, Papua Province. The research method used a qualitative approach, data collection techniques are observations, interviews, and documentations. The sources in this study are the Head of the Jayapura Regency Village Community Empowerment Office, the Head Sub-Section of Village and Traditional Village Governance Office, the Head of Yoboi Traditional Village Government, the Chief of Yoboi Traditional Village, A Member of C Comission of the Jayapura Regency People’s Representative Council and The Village community. The results of this research are: 1) The policy implementation of Yoboi Traditional Village change of status has not been effective. This can be seen from the fact that; there are not enough supporting resources (human, facilities, and budget), during implementing the traditional village system there is still an overlap of duties and functions between the Head of the Traditional Village and the Head of the Government Village (parent village), and lack of supervisory function by The Jayapura Regency People’s Representative Council 2) Supporting factors: a) There is support for legality, legal protection, b) There are supports from the community, religious leaders, traditional leaders, community leaders and academics, c) There are supports from the local government elites, d) There is support for motives in an effort to improve the welfare of the indigenous Papuans (OAP), e) There is support for Fiscal Spoil (fiscal incentives) f) There is eligibility in the conditions for changing the status of the village. Inhibiting factors: a) There are still overlaps of main tasks, functions and responsibilities between the Head of Traditional Village and the Head of Government Village (parent village), b) There are rejections from the community towards Yoboi Village change of status c) The community’s pessimisms that Yoboi Traditional Village change of status will be used as business means by political elites. 3) Policy implications of changing the status of Yoboy government Village to Traditional Village: a) There is recognition and respect for the village b) The preservation of the customs, traditions, and culture of the village community, c) The increase in public services, d) The realization of the effectiveness of implementation of Traditional Village Government, e) The growing role of The Village Communities, g) Ambigious distribution of powers, main duties and responsibilities, h) Limited work facilities and service facilities.